2011
DOI: 10.17533/udea.vitae.10653
|View full text |Cite
|
Sign up to set email alerts
|

INHIBITORY EFFECTS OF PLANT COMPOUNDS ON ENZYMATIC AND ACTIVITIES INDUCED BY A SNAKE PHOSPHOLIPASE A<SUB>2</SUB>

Abstract: Polyphenolic compounds have shown to inhibit toxic effects induced by snake venom proteins. In this work, we demonstrate that gallic acid, ferulic acid, caffeic acid, propylgallate and epigallocatechingallate inhibit the enzymatic activity of a phospholipase A2 (PLA2), using egg yolk as substrate. The IC50 values are between 0.38 – 3.93 mM. These polyphenolic compounds also inhibit the PLA2 enzymatic activity when synthetic substrate is used. Furthermore, these compounds decreased the cyotoxic effect induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 16 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Furthermore, hyaluronidase activity in all Micrurus venoms was confirmed, as evidenced by bands around 67.9-75.9 kDa, suggesting that there is substantial dispersion in situ; hyaluronidase activity is based on the degradation of hyaluronic acid, which is present in the extracellular matrix and acts as a spreading factor [60]. Approximately 5% of the proteome of M. helleri comprised hyaluronidases, which was indicated by the marked degradation bands in the zymogram.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, hyaluronidase activity in all Micrurus venoms was confirmed, as evidenced by bands around 67.9-75.9 kDa, suggesting that there is substantial dispersion in situ; hyaluronidase activity is based on the degradation of hyaluronic acid, which is present in the extracellular matrix and acts as a spreading factor [60]. Approximately 5% of the proteome of M. helleri comprised hyaluronidases, which was indicated by the marked degradation bands in the zymogram.…”
Section: Discussionmentioning
confidence: 78%
“…Two approaches were used to assess the PLA 2 activity. First, a 10% (w/v) egg yolk solution in agarose was made; once the solution solidified, 5 µg of the venom of each Micrurus species was seeded into circular wells in solution, solidified, and incubated for 1 h at 37 • C [60]. Crotalus durissus cumanensis venom from the Magdalena Medio ecoregion was used as a positive control, and phosphate saline buffer (pH 7.4) was used as a negative control.…”
Section: Phospholipase a 2 Activitymentioning
confidence: 99%
“…Snake venom phospholipases A 2 (svPLA 2 ) are enzymes which hydrolyze phospholipids and induce several pharmacological effects including edema, modulation of platelet aggregation, neurotoxicity, and myotoxicity (Six and Dennis, 2000;Kini, 2003;Pereanez et al, 2011). The present study observed that extracts and fractions of C. africana, S. obtusifolia, V. glabra, and W. ugandensis effectively neutralized svPLA 2 s in BAV, NAV, and NSV.…”
Section: Discussionmentioning
confidence: 57%